Proceedings of the 3rd International Conference on Quality of Service in Heterogeneous Wired/Wireless Networks - QShine '06 2006
DOI: 10.1145/1185373.1185376
|View full text |Cite
|
Sign up to set email alerts
|

What is the right model for wireless channel interference?

Abstract: In a wireline network, nodes form links with only those nodes they are wired to, and the links do not interfere with one another. In contrast, in a wireless network, signal transmissions are intrinsically broadcast, and suffer from mutual interference. In several physical layer technologies, a wireless signal is decoded by treating the sum of all the other on-going signal transmissions as noise. Hence, from a networking standpoint, there is a need to model wireless channel interference. An accurate interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 18 publications
2
79
0
1
Order By: Relevance
“…the users with data rate requirements) [13], utilising physical interference model [16] in the downlink of femtocell networks. Different required data rates are utilised to distinguish the priorities of different users.…”
Section: Introductionmentioning
confidence: 99%
“…the users with data rate requirements) [13], utilising physical interference model [16] in the downlink of femtocell networks. Different required data rates are utilised to distinguish the priorities of different users.…”
Section: Introductionmentioning
confidence: 99%
“…This model is a simplification of a physical wireless communication model but still takes into account both signal interference and signal fading. For other types of wireless channel interference models, refer to Iyer et al (2009).…”
Section: A Protocol Communication Modelmentioning
confidence: 99%
“…A transmission on link (u, v) is successful if SINR of the signal received at v is greater than a predefined threshold. In [40], the authors showed that the interference range model with Table 3 summarizes the results of the complexity analyses presented in this section.…”
Section: Interference Range Model [40] In Multi-channel Networkmentioning
confidence: 99%